2015
DOI: 10.21825/af.v28i2.4866
|View full text |Cite
|
Sign up to set email alerts
|

A review of factors associated with the utilization of healthcare services and strategies for improving postpartum care in Africa

Abstract: Reducing maternal mortality continues to be a major challenge for African countries. We conducted a literature review to identify the factors associated with the utilization of maternal and child healthcare services during the postpartum period and the strategies for strengthening postpartum healthcare in Africa. We carried out an electronic search in several databases of texts published between 1995 and 2012 related to maternal and child health. Seventyfive publications fitted the eligibility criteria. Our an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 57 publications
(195 reference statements)
2
17
2
Order By: Relevance
“…Young mothers more likely utilize postnatal care service than older one. This finding is supported by local studies conducted in Wolayitta Zone, SNNPR [11], and in addition it is similar with a study conducted in Pakistan [16], from a review on African country [17]. This can be justified younger mothers are more likely to have greater exposure and more access to education.…”
Section: Discussionsupporting
confidence: 87%
“…Young mothers more likely utilize postnatal care service than older one. This finding is supported by local studies conducted in Wolayitta Zone, SNNPR [11], and in addition it is similar with a study conducted in Pakistan [16], from a review on African country [17]. This can be justified younger mothers are more likely to have greater exposure and more access to education.…”
Section: Discussionsupporting
confidence: 87%
“…In LMICs, the lack of a pre-discharge check may partly be a result of inadequate staffing, particularly in lower-level facilities, where odds of receiving the check were lower because providers are busy assisting other women in labor or with complications [15,37]. Already overburdened or burned-out staff [38] may see postpartum care and pre-discharge checks as a less important priority compared to providing antenatal and intrapartum services [11].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current literature on coverage and quality of postpartum care focuses on women who gave birth outside of health facilities and on their newborn [1113]. Much less is known about the quality of care for women within health facilities during the immediate postpartum period before discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its importance, it is the most neglected maternal health service particularly in developing countries [6][7][8][9]. The Demographic and Health Survey (DHS) results of different African countries indicated that only 36% of women had a postnatal visit within 2 days [10] but, it was much less in Ethiopia which was 17% according to 2016 EDHS [11].…”
Section: Introductionmentioning
confidence: 99%